Safety and efficacy of triple therapy with peginterferon, ribavirin and boceprevir within an early access programme in Spanish patients with hepatitis C genotype 1 with severe fibrosis: SVRw12 analysis. (15th September 2014) - Calleja, Jose L.; Pascasio, Juan M.; Ruiz‐Antorán, Belén; Gea, Francisco; Bárcena, Rafael; Larrubia, Juan R.; Pérez‐Álvarez, Ramón; Sousa, Jose M.; Romero‐Gómez, Manuel; Solá, Ricard; de la Revilla, Juan; Crespo, Javier; et al.
Abstract Background & Aims The addition of protease inhibitors (PIs) changed the hepatitis C virus (HCV) treatment standards and improved sustained viral response (SVR) rates in patients with genotype 1 HCV infection. Methods Prospective, multicentre, national registry that includes naïve and treatment‐experienced patients with HCV genotype 1 infection, who had bridging fibrosis or cirrhosis and were treated with triple therapy (peginterferon alfa‐2a or alfa‐2b, ribavirin and boceprevir) as compassionate use, and in accordance with the Summary of Product Characteristics. Results Most of the patients (68.2%) were male, with a mean age of 53 years, 75% (n = 128) had HCV 1b genotype and baseline viral load of 6.2 log. According to prior treatment, 20% of patients were treatment‐naïve and 80% had received prior treatment. Approximately 36.5% of patients (n = 62) reported at least one serious adverse events (SAEs) (total SAEs = 103). The most common SAEs were neutropenia (57.6%), anaemia (47.6%) and grade 3 thrombopenia (25.9%). Patients with albumin <3.5 g/dl and bilirubin >2 mg/dl had an increased relative risk (greater than one‐fold) for SAEs, including infections and hepatic decompensation. In the intent‐to‐treat analysis (n = 170), the overall percentage of patients with SVRw12 was 46.5%. In patients with 1 log decrease at week 4 (lead‐in phase), the overall SVRw12 rate was 67.0%. In the patients initiating triple therapy with boceprevir (n = 139), the global response rate was 56.4%. In a multivariate analysis, an increased probability of achieving SVR was associated with response to prior treatment (relapsers), >1 log decrease in viral load in the lead‐in phase and baseline albumin >3.5 g/dl. Conclusions Triple therapy in patients with severe fibrosis/cirrhosis is associated with a higher rate of SAE and a lower rate in comparison with patients with mild disease. However, for patients with intact liver function, it could be considered as a treatment option, when other alternatives would not be available.